Pengaruh Work-life Balance dan Work Stress Terhadap Turnover Intention dengan Work Environment sebagai Variabel Mediasi Generasi Milenial Di Kalimantan Barat - Aspandi, Sutri Murdiana; Karsim, Karsim; Mufrihah, Mazayatul; Saputra, Pramana (Primary Journal of Multidisciplinary Research, 2025)
This study seeks to examine the impact of work-life balance and occupational stress on turnover intention, with the work environment serving as a mediating variable. This study employs a quantitative methodology. The employed sample approach is purposive sampling. This research's population comprises 151 millennial respondents from West Kalimantan. The study employs Structural Equation Modelling (SEM) analysis utilising SMARTPLS 4 software. The research findings indicate that work-life balance adversely and significantly influences turnover intention. Occupational stress exerts a favourable and substantial influence on turnover intention. The equilibrium between work and personal life positively and significantly influences the work environment. Occupational stress adversely and substantially impacts the work environment. The work environment adversely and substantially influences turnover intention. The work-life balance adversely and significantly influences turnover intention via the work environment. Work-related stress exerts a favourable and substantial influence on turnover intention via the work environment. This research indicates that increased employee stress correlates with a heightened propensity to resign. A supportive and cheerful workplace can mitigate the adverse effects of work-related stress and enhance work-life balance, hence decreasing the propensity to resign.